Progettazione e sperimentazione in classe di una sequenza didattica sui concetti di dipolo permanente e istantaneo - Cimadamore, Nicolò; Ghirardi, Marco; Regis, Alberto; Ghibaudi, Elena (Chimica nella Scuola, 2025)
The intertwining of chemical epistemology and didactics may foster educational approaches capable to overcome conceptual problems in chemistry. We discuss some aspects of this relationship and present the theoretical framework adopted for designing a teaching sequence on intermolecular forces.